Mimesis and Colonialism: Emerging Perspectives on a Shared History - Roque, Ricardo (2015)
Mimesis is an important human faculty and a fertile concept in Western intellectual traditions. Colonialism is a critical and lasting event in the history of European societies and their relationship with the wider world. This essay examines the significance of telling the shared history between these two phenomena. It surveys historical and anthropological literature that explores mimesis, imitation and mimicry as concepts and as practices in the history of European colonial and imperial expansionism, across three connected themes: indigenous resistance and anti-colonialism; the making of identity and alterity in colonial encounters and post-colonial relationships; and, finally, the presence of mimesis as theory and practice of empirebuilding and colonization.